Intimations : [large type] six essays - Smith, Zadie (Thorndike Press, a part of Gale, a Cengage Company, 2020)
"Written during the early months of lockdown, Intimations explores ideas and questions prompted by an unprecedented situation. What does it mean to submit to a new reality--or to resist it? How do we compare relative sufferings? What is the relationship between time and work? In our isolation, what do other people mean to us? How do we think about them? What is the ratio of contempt to compassion in a crisis? When an unfamiliar world arrives, what does it reveal about the world that came before it?"--